Social Stigma Against Tuberculosis Patients and Its Impact on Patient Mental Health: A Sociological and Public Health Analysis (International Journal of Economics Management and Social Science, 2026)
Tuberculosis (TB), despite being a preventable and curable infectious disease, carries a heavy burden of social stigma in Indonesia that profoundly undermines patient mental health, treatment adherence, and public health outcomes. This study investigates the forms, sources, and mental health consequences of TB-related social stigma in North Sumatra Province, employing a mixed-methods design combining a quantitative survey (n = 274 TB patients) with qualitative phenomenological interviews (n = 30). The Social Stigma Scale for TB (SSS-TB), developed and validated for this study (α = 0.88), measured enacted, anticipated, and internalized (self) stigma. The Depression Anxiety Stress Scale-21 (DASS-21) assessed mental health outcomes. Results demonstrate that 79.2% of patients experienced at least one form of enacted stigma, with self-stigma demonstrating the strongest association with depression (r = 0.741, p < 0.001). Structural equation modeling reveals that social support buffers the stigma-mental health pathway (β = −0.312, p < 0.001), while treatment completion mediates the long-term effects. Qualitative themes illuminate shame, social isolation, occupational discrimination, and the particular stigma burden of TB's association with poverty and suspected moral failing. The study calls for integrating TB stigma reduction into the national TB elimination program and recommends community-based psychosocial support as an essential complement to biomedical treatment. Keywords: tuberculosis; social stigma; mental health; depression; Indonesia; North Sumatra; public health; stigma reduction; self-stigma